Self-controlled feedback is effective if it is based on the learner’s performance: a replication and extension of Chiviacowsky and Wulf (2005) - Carter, Michael J.; Carlsen, Anthony N.; Ste-Marie, Diane M. (Frontiers in Psychology, 2014)
The learning advantages of self-controlled feedback schedules compared to yoked schedules have been attributed to motivational influences and/or information-processing activities with many researchers adopting the motivational perspective in recent years. Chiviacowsky and Wulf (2005) found retention performance could be equally optimized when the feedback decision was made before (Self-before) or after a trial (Self-after), but that superior transfer occurred only when it was made after a trial. They concluded that motivational factors resulted in similar retention, but superior skill transfer was hypothesized to emerge from information-processing activities, like error estimation. Here, we tested whether a positive additive effect of motivational and informational processes could produce greater learning benefits under self-controlled feedback conditions. We therefore included a Self-Both group that was able to request feedback before a trial but could change or stay with their original choice after the trial. We maintained the Self-Before and Self-After groups used by Chiviacowsky and Wulf and added corresponding yoked groups for the three self-controlled groups. Participants practiced a targeted aiming task whereby a slider was propelled down a track to a target distance. Contrary to the additive hypothesis, the Self-Both group did not outperform the other Self-controlled groups. Instead, similar retention and transfer scores were found in the Self-Both and Self-After groups, yet both groups demonstrated superior learning compared to the Self-Before group and their respective Yoked groups (p’s < .05). These findings suggest that information-processing activities may have a greater relative contribution to the learning benefits of self-controlled feedback schedules than motivational factors.